Tax Liabilities in Small Business and Private - Murotjonova Mubina Dilshod qizi (Zien Journals, 2022)
This article discusses small business and private entrepreneurship in the Republic of Uzbekistan, its current issues in public life, the tax system in the legislation on small business and entrepreneurship, the laws adopted in the field of this activity since independence and amendments to them.
Keywords: New Uzbekistan econom; small business; privatization; tax system